MESIN PENGIRIS PISANG DENGAN VARIASI DIAMETER PULLY TERHADAP PUTARAN DAN TEBAL IRISAN - Edi Handoyo; Catur Pramono; Xander Salahudin; Sri Hastuti (Universitas Tidar, 2019)
This research is based on the background of many banana slicing machines needed by home industries. Therefore, to increase production capacity, simplify work and shorten work time with optimum results new innovations are needed. The purpose of this study was to make a prototype of a banana slicing machine with variations in pulley diameter to the rotational speed and thickness of the slices and to know the capacity of the banana slicing machine. The prototype of a banana slicing machine made using a 1400 rpm electric motor is assembled with a 40 mm pulley, to reduce the v-belt rotational speed to pulley with a diameter of 125 mm pulley, 150 mm, 175 mm. The capacity of the first pulley slices at a speed of 448 rpm, the pulley diameter of 125 mm is 7.66 grams / second and the slice thickness is 2 mm. The sliced capacity of the second pulley uses a 150 mm pulley diameter of 6.42 grams / second and a slice thickness of 1-2 mm. The capacity of the third pulley slice uses a 175 mm pulley diameter of 5.51 kg / hour and a slice thickness of 1 mm and not a rule.